Dimensões culturais envolvidas na busca pelo parto natural humanizado - Araújo, Bárbara Régia Oliveira de (2016)
From the assumptions found in Madeleine Leininger’s Transcultural Nursing Theory, the current work analized the cultural dimensions that influenced on women’s search of natural humanized birth, in Maceió – AL, considering the potential of cultural studies to support culturally congruent practices. This is a qualitative and descriptive study, made between december 2015 and april of 2016 in Maceió - AL. 14 (fourteen) women, who sought or not a natural humanized birth in said context, are our informants of this research. For information gathering a semistructured interview form was used based on the theoretical referential, that propitiated the survey of cultural meanings analyzed in its universality and diversity, in order to meet this research objective. From the results analysis, it was possible to identify whether or not the search for a natural humanized birth permeates the meaning of parturition to the informants taking into account their realities and health contexts. The cultural dimensions involved that guided their choices: 1) Their ideologies and beliefs, directing a way of life that guides them according to their desires to enjoy full autonomy of their bodies and that, even when they delegate their health processes to other people, they do it according to positively valued experiences and care; 2) Class issues, access to information, technology and public health policies, whose differences are mitigated by the social differences from a capitalist society; 3) Meanings and experiences of your support networks, which are present in all other dimensions.